Bibliometric Analysis of Aluminium Oxide Nanoparticle in Biomedical Applications - Zahrah Rufaida; Asep Bayu Dani Nandiyanto (Advance Sustainable Science Engineering and Technology, 2022)
Aluminium oxide nanoparticles are materials that can be used in various applications, for example in biomedicine. The purpose of this study was to determine research trends on Al2O3 nanoparticles in biomedical applications using bibliometric analysis. The data used in this study was obtained from Google Scholar using the Publish or Perish reference manager and data visualization using VOSviewer. The data obtained were based on the keywords Al2O3 nanoparticle, aluminium oxide nanoparticle, and biomedical application. Based on the analysis, we found 987 articles relevant to the keywords from 2012–2022. The results show that research on Al2O3 nanoparticles in biomedical applications from 2012–2022 tends to increase with the most articles in 2012, as many as 196 articles. This bibliometric analysis is expected to help other researchers who will conduct research on the same theme as discussed in this article.